2017
DOI: 10.18632/oncotarget.21108
|View full text |Cite
|
Sign up to set email alerts
|

The clinical use of the platelet to lymphocyte ratio and lymphocyte to monocyte ratio as prognostic factors in renal cell carcinoma: a systematic review and meta-analysis

Abstract: Conflicting evidence exists regarding the effect of platelet to lymphocyte ratio (PLR) and lymphocyte to monocyte ratio (LMR) on the prognosis of renal cell carcinoma (RCC) patients. Here we quantify the prognostic impact of these biomarkers and assess their consistency in RCC. Eligible studies were retrieved from the PubMed, Embase and Web of Science databases. Pooled hazard ratios (HRs), odds ratios (ORs), and 95% confidence intervals (CIs) were calculated. Sixteen studies containing 6,223 patients met crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 30 publications
1
29
2
1
Order By: Relevance
“…The nutrition-and inf lammation-based prognostic scores examined in this study were the following: CRP/Alb ratio (CRP measured in mg/L and albumin measured in g/L 26 ); CRP/PAlb ratio (prealbumin measured in g/L); mGPS, which is a combination of CRP and albumin (patients with a normal albumin level (≥ 3.5 g/L) and normal CRP level (≤ 10 mg/L) were allocated a score of 0, patients with an elevated CRP level (> 10 mg/L) and a low albumin level (< 3.5 g/L) were allocated a score of 1, and patients with both a low albumin level (< 3.5 g/L) and elevated CRP level (> 10 mg/L) were allocated a score of 2 27 ); NLR 16 ; PLR 28 ; LMR, 29 and prognostic nutritional index (PNI), which was calculated by the formula 10 × albumin (g/dL) + 0.005 × lymphocyte count/µL. 30 All indicators involved in the calculation of the nutrition-and inflammationbased prognostic scores were derived within the 5 days prior to surgery.…”
Section: Inflammation Markersmentioning
confidence: 99%
“…The nutrition-and inf lammation-based prognostic scores examined in this study were the following: CRP/Alb ratio (CRP measured in mg/L and albumin measured in g/L 26 ); CRP/PAlb ratio (prealbumin measured in g/L); mGPS, which is a combination of CRP and albumin (patients with a normal albumin level (≥ 3.5 g/L) and normal CRP level (≤ 10 mg/L) were allocated a score of 0, patients with an elevated CRP level (> 10 mg/L) and a low albumin level (< 3.5 g/L) were allocated a score of 1, and patients with both a low albumin level (< 3.5 g/L) and elevated CRP level (> 10 mg/L) were allocated a score of 2 27 ); NLR 16 ; PLR 28 ; LMR, 29 and prognostic nutritional index (PNI), which was calculated by the formula 10 × albumin (g/dL) + 0.005 × lymphocyte count/µL. 30 All indicators involved in the calculation of the nutrition-and inflammationbased prognostic scores were derived within the 5 days prior to surgery.…”
Section: Inflammation Markersmentioning
confidence: 99%
“…PLR and LMR are inflammatory markers that consist of the peripheral blood cells count besides NLR. Several studies have shown that high PLR is associated with shorter OS and PFS . High LMR was reported to be associated with superior OS and PFS, and the MSKCC model and IMDC model were improved by incorporating LMR into them …”
Section: Parameters Associated With Inflammationmentioning
confidence: 99%
“…Several studies have shown that high PLR is associated with shorter OS and PFS. 73,74 High LMR was reported to be associated with superior OS and PFS, and the MSKCC model and IMDC model were improved by incorporating LMR into them. 75 SII is a novel inflammation index, which was defined as follows: Plt 9 Neu / lymphocyte count.…”
Section: Inflammatory Indexes Consisting Of Peripheral Blood Cellsmentioning
confidence: 99%
“…One of the net index of the systemic inflammation status is an increased neutrophil-to-lymphocyte ratio (NLR), on this basis, there are studies showing that high NLR level indicates poor prognosis (12), especially in solid tumors such as small cell lung cancer (13), colorectal (14), hepatocellular carcinoma (15,16) and ovarian cancer (17). Studies on RCC and NLR showed that inflammation plays an important role in the pathogenesis and progression of RCC (18) and also neutrophils and platelets have a prominent role in the tumor formation and development. So NLR, platelets and neutrophil levels are an easily available and cheap laboratory parameters that have the potential to become a cost effective biomarker to predict disease progression.…”
Section: Introductionmentioning
confidence: 99%